2020
DOI: 10.1177/2382120520981979
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Full-length Practice Exams for the New MCAT Exam for Premedical Students

Abstract: Objective: To investigate whether full-length practice exams could predict performance in the new MCAT exam in a pilot group. Methods: A dataset of the first group of students who enrolled in the premedical post-baccalaureate program, established at Khalifa University of Science and Technology in the 2018-2019 academic year, were used. Nineteen students from the group were subsequently admitted to the newly launched Doctor of Medicine Program at KU in the 2019 fall semester. Results: Performance in the full-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The demand for practice exam content is continuously growing. Research has shown that increasing the use of full-length MCAT practice exams correlates positively with MCAT performance 23 . Future research may examine if LLMs can relieve some of the laborious human efforts in creating these practice tests by helping with the question-explanation writing process or even producing entire exam passages independently.…”
Section: Discussionmentioning
confidence: 99%
“…The demand for practice exam content is continuously growing. Research has shown that increasing the use of full-length MCAT practice exams correlates positively with MCAT performance 23 . Future research may examine if LLMs can relieve some of the laborious human efforts in creating these practice tests by helping with the question-explanation writing process or even producing entire exam passages independently.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we have examined the value of practice exams as a predictor of performance on the actual MCAT exam. We observed that these exams may be a good indicator of actual performance, 17 and thus, this method can provide us multiple opportunities to gauge performance. Specifically, admissions committees can consider administering multiple remotely proctored MCAT practice exams that can provide trend data for a longitudinal evaluative approach, while simultaneously enhancing skills needed for future standardized exams.…”
Section: Current Need For Exam Alternativesmentioning
confidence: 97%
“… 5 To compound matters, the faculty, staff and students (premedical and medical) associated with the College of Medicine and Health Sciences (CMHS) had to rapidly and fully transition to e-learning while addressing challenges associated with developing a new medical school that provided US-style education for the first time in the nation’s history. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…5 To compound matters, the faculty, staff and students (premedical and medical) associated with the College of Medicine and Health Sciences (CMHS) had to rapidly and fully transition to e-learning while addressing challenges associated with developing a new medical school that provided US-style education for the first time in the nation's history. 6,7 As a college still in its infancy, our first cohort of medical students was, at that time, transitioning from their first to their second year of medical school. Our second cohort of medical students and a new cohort of premedical students were in their first year of study.…”
Section: Introductionmentioning
confidence: 99%